Microorganism and filamentous fungi drive evolution of plant synapses - Baluska, Frantisek; Mancuso, Stefano (Frontiers in Cellular and Infection Microbiology, 2013)
In the course of plant evolution, there is an obvious trend toward an increased complexity of plant bodies, as well as an increased sophistication of plant behavior and communication. Phenotypic plasticity of plants is based on the polar auxin transport machinery that is directly linked with plant sensory systems impinging on plant behavior and adaptive responses. Similar to the emergence and evolution of eukaryotic cells, evolution of land plants was also shaped and driven by infective and symbiotic microorganisms. These microorganisms are the driving force behind the evolution of plant synapses and other neuronal aspects of higher plants; this is especially pronounced in the root apices. Plant synapses allow synaptic cell–cell communication and coordination in plants, as well as sensory-motor integration in root apices searching for water and mineral nutrition. These neuronal aspects of higher plants are closely linked with their unique ability to adapt to environmental changes.